Effect of Additive Elements Bi/Ni/Ge on Crack Initiation and Propagation for Low-Ag Solders (Fracture and Structural Integrity, 2018)
This study discusses an effect of additive elements on crack propagation behaviour for low-Ag contain Sn1.0Ag0.7Cu lead-free solders at high temperature. A cyclic push-pull loading tests for four kinds of Sn1.0Ag0.7Cu solders were conducted at 313 K with a single hole specimen. Stress amplitude of solders containing additive element Bi were bigger than that of Bi-free solders. Crack initiation cycle of solders containing Bi were earlier than that of Bi-free solders. Low-Ag solders containing Bi had shorter crack propagation cycles than that of Bi-free solders. These results indicate that the additive element Bi have the effects on the crack initiation and propagation cycles, that is, Bi accelerates the crack propagation rate. We also discuss the adaptation of J-integral range parameter to the crack propagation rate evaluation for solders. J-integral range parameter evaluates the crack propagation rate for low-Ag solders independent of the additive elements.
Keywords: Additive elements; Crack initiation; Crack propagation; Lead-free solder; Low-Ag